1979
DOI: 10.2466/pr0.1979.44.3.823
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault in a Prison

Abstract: The fact that only 12 of 1100 inmates were identified by staff as having sexually assaulted other inmates over a 12-mo. period suggests that sexual assault may not be a frequent problem in federal prisons. However, implications regarding the racial compositions of the assaulters and victims noted in the present study may represent a problem more in need of study than is that of sexual assault per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Attempted sexual assault 2 -28% Davies, 1968;Lockwood, 1978Lockwood, , 1980Nacci & Kane, 1983Tewksbury, 1989 Sexual assault 1 -14% Cooley, 1993;Davies, 1968;Heilpern, 1994;Maitland & Sluder, 1998;Nacci & Kane, 1983Wooden & Parker, 1982 Rape <1% Moss, Hosford, & Anderson, 1979;Nacci & Kane, 1983 Murder <.01% Ekland-Olson, 1986;Fleisher, 1994;Jayewardene & Doherty, 1985;Porporino, Doherty, & Sawatsky, 1987 Psychological Victimization…”
Section: Discussionmentioning
confidence: 99%
“…Attempted sexual assault 2 -28% Davies, 1968;Lockwood, 1978Lockwood, , 1980Nacci & Kane, 1983Tewksbury, 1989 Sexual assault 1 -14% Cooley, 1993;Davies, 1968;Heilpern, 1994;Maitland & Sluder, 1998;Nacci & Kane, 1983Wooden & Parker, 1982 Rape <1% Moss, Hosford, & Anderson, 1979;Nacci & Kane, 1983 Murder <.01% Ekland-Olson, 1986;Fleisher, 1994;Jayewardene & Doherty, 1985;Porporino, Doherty, & Sawatsky, 1987 Psychological Victimization…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in international settings, particularly studies focusing on HIV/AIDS prevention, have demonstrated that prisons can be harmful environments in terms of epidemics and public health (Sagarin, 1976;Moss et al, 1979;Douglas et al, 1989;Wiggs, 1989;Carbajal et al, 1991;Guerena Burgueno et al, 1992;Ducos et al, 1993;Anonymous, 1998;Odujinrin & Adebajo, 2001;Chen et al, 2003;Green et al, 2003). Thus, if LGBT persons are at high risk of exposure to prison environments, they are similarly at high risk for exposure to the various risks associated with being incarcerated.…”
Section: Incarceration and Lgbt Healthmentioning
confidence: 99%
“…No studies have attempted to establish the frequency of male rape through a systematic examination of official records (i.e., incident reports or protective custody records). And although a few studies have included rapists in their analyses (Lockwood, 1980;Moss, Hosford, & Anderson, 1979;Nacci & Kane, 1983, 1984a, 1984b, these samples are disturbingly small since rapists are difficult to identify and study. Therefore, the overwhelming majority of quantitative research on male rape has relied upon victimization surveys that have been conducted in one of two manners.…”
mentioning
confidence: 97%